Early-onset endothelin receptor blockade in hypertensive heterozygous Ren-2 rats - Vanecková, Ivana; Kramer, Herbert J; Bäcker, Angela; Schejbalová, Stanislava; Vernerová, Zdena; Eis, Václav; Opocenský, Martin; Dvorák, Pavel; Cervenka, Ludek (Vascular pharmacology, 2006)
Male heterozygous Ren-2 transgenic rats and Hannover Sprague-Dawley rats fed a normal or high-salt diet were either untreated or treated with the nonselective receptor ET(A)/ET(B) receptor blocker bosentan or the selective ET(A) receptor blocker, ABT-627, known as atrasentan. Survival rate was partly increased by bosentan and fully normalized by atrasentan. Bosentan did not significantly influence the course of hypertension in TGR, whereas atrasentan significantly decreased BP on both diets. Atrasentan substantially reduced proteinuria, cardiac hypertrophy, glomerulosclerosis and left ventricular ET-1 tissue concentration on both diets. Our data indicate that ET(A) receptor blockade is superior to nonselective blockade in attenuating hypertension, end-organ damage and improving survival rate.
Keywords: Proteinuria; Animals; heterozygot; receptory endotelinů; hypertenze; Sodium Chloride, Dietary; Receptors, Endothelin; Animals, Genetically Modified; kuchyňská sůl; Glomerulosclerosis, Focal Segmental; pyrrolidiny; Atrasentan; Renin; Endothelin B Receptor Antagonists; časové faktory; Time Factors; Heterozygote; atrasentan; Cardiomegaly; Pyrrolidines; Sulfonamides; Bosentan; krevní tlak; antagonisté endotelinového receptoru B; Rats, Sprague-Dawley; Endothelin Receptor Antagonists; tělesná hmotnost; Hypertension; antagonisté endotelinového receptoru; Male; modely nemocí na zvířatech; bosentan; potkani Sprague-Dawley; sulfonamidy; Disease Models, Animal; krysa rodu Rattus; Body Weight; endotelin-1; kardiomegalie; Antihypertensive Agents; Endothelin-1; zvířata; mužské pohlaví; antihypertenziva; antagonisté endotelinového receptoru A; geneticky modifikovaná zvířata; Blood Pressure; fokálně segmentální glomeruloskleróza; Endothelin A Receptor Antagonists; renin; Rats; proteinurie